Proceso de atención de enfermería en paciente de 21años con aborto incompleto más anemia severa. - Arias Gaibor, Wilder Kennedy (2023)
This clinical case study focuses on the intervention of a patient with an incomplete abortion, one of the problems that is present in developing countries and therefore represents one of the greatest demands in the areas of obstetric emergencies. The most common symptoms in patients with incomplete abortion are vaginal bleeding, colicky pain of different degrees, pelvic pain, and complications such as sepsis, perforation of the uterus, injuries to the genitals, or injuries to other internal organs. Iron deficiency anemia occurs when the body does not have enough iron. Iron helps make red blood cells. Anemia is the decrease in the mass of blood cells or the concentration of circulating hemoglobin in the blood, it is not a good diagnosis according to the number of red blood cells, due to variations in size experienced. The present clinical case covers the management of a 21-year-old patient, who comes to the medical service and through exploration reports an enlarged uterus with an enlarged endometrium, a heterogeneous image inside with a negative low-density Doppler echo whose clinic corresponds to ovular remnants due to incomplete abortion. The present clinical case covers the management of a 21-year-old patient, who goes to the medical service and through exploration reports an enlarged uterus with an enlarged endometrium, a heterogeneous image inside with a negative low-density Doppler echo whose clinic corresponds to ovular remains due to incomplete abortion. That is why the proposed activities are to identify the risk factors that lead to presenting this obstetric complication, so that women obtain more knowledge and can prevent it as much as possible or recognize it in a timely manner if it occurs, in this way they can take Appropriate decisions, approach the health center as soon as possible so that the health team can take the appropriate measures.